MULTIPARAMETRIC APPROACHES TO DIAGNOSING FUNCTIONAL STATUS OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND SYSTEMIC SCLERODERMA - Drohomeretska, O.I.; Kuryliv, H.M.; Hrydzhuk, T.I.; Herych, P.R.; Didushko, O.M. (World of Medicine and Biology, 2019)
It has been established that among the visceral pathology in systemic scleroderma and systemic lupus erythematosus, the key role is played by the heart damages. For early diagnosis of heart failure in these pathologies, the most informative are electrocardiography and echocardioscopy with the transmitral blood flow study. At the same time, in the vast majority of patients, the specific features of the left ventricle structural-geometric changes are normal cavities with the walls hypertrophy and the preserved pumping function, but the diastolic function is significantly disordered. Development of the chronic heart failure in such patients is due to the natural evolution of the transmitral blood flow spectrum from the normal type through hypertrophic and pseudonormal to the decompensated (restrictive) one.